A Canonical Correlation Analysis: Learning Preferences and Sensory-Specific English Learning Material Stimuli - Shi, Yi-shan; Tsai, Chih-yung (Revija za elementarno izobraževanje, 2022)
The study investigated the relationship between sensory-specific English learning material stimuli and sensory learning preferences. The study involved 53 English as a foreign language participants. Participants were provided with different sensory-specific English learning material stimuli to analyse their overall comprehension. A canonical correlation analysis was used to analyse the collected data statistically. Auditory learning preference was significantly related to adaptive English learning stimuli (paper texts with sound, images with captions, and sound with images). The canonical correlation coefficient of .665 indicated 44.2% of the variance in English learning was determined by learners with auditory learning preferences and adaptive learning materials.